Study on the deformation homogeneity and electrical conductivity in Co-CR-Ni-Mo wires drawn with different drawing practices - Gvk, Sai Srikanth (2020)
This study investigates the influence of cold wire drawing practices namely full die drawing (FDD) and half die drawing (HDD) on the deformation homogeneity in Co-35Ni-20Cr-10Mo alloy (MP35N) wires which are used for manufacturing implantable medical products. The inhomogeneous factor was used to assess the level of inhomogeneity in the wires, and electrical conductivity was measured on the wires, after drawn to different cold work (CW) reductions and with different drawing practices. Electron beam scattered diffraction, field emission scanning electron microscope and transmission electron microscope characterization were performed on the wire samples to correlate the mechanical and electrical properties to their texture and grain size. The results of this study conclude that the wires drawn with the FDD practice exhibited homogenous deformation, uniform microstructural and hardness gradient across the wire when compared to HDD wires. The electrical conductivity of the HDD-drawn wires was higher than the FDD wires and the level of inhomogeneity and the variation of conductivity decreased with the increase in CW.